Perubahan Sosial Ekonomi Masyarakat Pasca Kehadiran Perumahan (Studi Di Kelurahan Bontoala Kec.Pallangga Kab.Gowa) - Rinaldi Rinaldi; Rahmat Nur; Muhammad Afdal; Fatmawati Fatmawati (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2024)
Social change is a reality that cannot be avoided by a society, including urban communities. Many factors drive social change, one of which is housing development. Housing development not only has an impact on the narrowing of urban land, but also brings socio-economic changes to the surrounding community. Because, housing development indirectly allows immigrant communities to bring values acculturated with the local community which has implications for changes in social structure. The purpose of this study was to examine how the socio-economic changes in the community after housing construction in the Bontoala Village, Pallangga District, Gowa Regency. This research uses a type of qualitative research with a descriptive qualitative approach. Collecting data through observation (observation) and interviews. Data analysis techniques through data reduction, data presentation, data interpretation, and conclusions. The results of this study indicate that the socio-economic changes in the community after housing construction in the Bontoala Village, Surabaya City, namely; First, a change in mindset, that is, what was originally irrational became a rational society. Second, changes in the behavior or lifestyle of the Bontoala people who tend to have a consumptive lifestyle. Third, changes in the livelihoods of the Bontoala people, which were originally in the agricultural sector, shifted to trade, industry and services. Fourth, changes in the function of the house, after housing construction, the function of the house is not only as a place to live, but also as an economic activity.